A dynamic by‐production framework for measuring productivity change in the presence of socially responsible and undesirable outputs: Evidence from European food processors. Issue 2 (31st January 2022) - Engida, Tadesse Getacher; Oude Lansink, Alfons G. J. M.; Rao, Xudong
Abstract: In the past decade, corporate firms have globally increasingly adopted corporate social responsibility (CSR) practices; however, so far less is known about how productivity change in the presence of socially responsible and undesirable output can be evaluated. This paper develops a framework that integrates CSR in a dynamic by‐production technology which captures the transformation of multiple inputs into marketed outputs, socially responsible and undesirable outputs, while accounting for adjustment costs in quasi‐fixed inputs. The paper illustrates the method using a sample of European food and beverage manufacturing firms. The results of the empirical application show that there is a decline in dynamic Luenberger productivity indicators mainly due to technical inefficiency change. Hence, firms should devise strategies to enhance utilization of resources and reduce technical inefficiency. The regression of productivity change indicators on firm‐specific factors showed that more indebted firms experienced a lower growth of the productivity of undesirable output, whereas more profitable firms have a lower productivity growth of variable inputs and a higher growth of the productivity of investments. [EconLit Citations: C02, C14, C6, D24]